Lercanidipine/enalapril combination in the management of obesity-related hypertension - Grassi G (Dove Medical Press, 2016)
Guido Grassi1,2 1Internal Medicine, Department of Health Science, Università Milano-Bicocca, Milano, Italy; 2Istituto di Ricerche a Carattere Scientifico (IRCCS) Multimedica, Sesto San Giovanni, Milano, ItalyAbstract: Obesity-related hypertension represents a condition frequently observed in current clinical practice characterized by a complex pathophysiological background and a very high cardiovascular risk profile, particularly in severely obese individuals. This explains, on the one hand, the difficulty in reducing elevated blood pressure values in this pathological state and, on the other, the need to achieve this goal in a relatively short-time period to prevent the occurrence of fatal and nonfatal cardiovascular events. Both nonpharmacological and pharmacological measures are available in the therapeutic approach for this condition. Among the pharmacological interventions, a combination of two antihypertensive drugs represents the most common recommended strategy aimed at achieving blood pressure control. This paper, after briefly examining the main pathophysiological features of obesity-related hypertension, will review the importance in the treatment of this condition of the drug combination based on a calcium channel blocker and an angiotensin-converting enzyme inhibitor, with specific focus on lercanidipine/enalapril. Following an analysis of the main pharmacological properties of the combination, the results of the studies based on this pharmacological approach in obesity-related hypertension will be critically discussed. The efficacy, safety, and tolerability profile of the lercanidine/enalapril drug combination as well as its potential limitations will also be examined.Keywords: obesity-related hypertension, antihypertensive drug treatment, combination drug, lercanidipine/enalapril